Inovasi Kurikulum Melalui Integrasi Ilmu Keagamaan dan Ilmu Pengetahuan di MTs Negeri 1 Probolinggo - Toyyibatul Mukminatus Sukriyah; Misbahul Arifin (Education Reserach Center, 2025)
This study focuses on curriculum innovation through the integration of religious knowledge and general science at MTs Negeri 1 Probolinggo. The aim is to understand the strategies and implementation of this integration in the learning process, as well as to assess its impact on strengthening students’ religious character and academic competence. The research employs a descriptive qualitative approach, utilizing data collection techniques such as observation, in-depth interviews, and document analysis. The findings reveal that MTs Negeri 1 Probolinggo has successfully developed an integrative curriculum model by embedding Islamic values into general subjects and presenting religious studies in a contextual manner related to scientific and social issues. This integration is reflected in lesson planning, the use of thematic teaching materials, and the implementation of extracurricular activities that support the synergy between the two fields of knowledge. The implications of this innovation are not only the enhancement of students’ holistic understanding but also the formation of balanced character development encompassing both spiritual and intellectual aspects. These findings may serve as a reference for other Islamic schools in designing curricula that are responsive to contemporary challenges without compromising religious values.